Esthetic Rehabilitation of a Non-Vital Discolored Tooth Through Endodontic Retreatment and Intra-Coronal Bleaching: A Case Report - Faber Sidabutar; Hendra D A Dharsono (SONDE (Sound of Dentistry), 2026)
Background: Discoloration of non-vital anterior teeth is a common aesthetic concern, often associated with inadequate root canal treatment. A combined approach involving non-surgery endodontic retreatment and walking bleaching offers a conservative solution to restore both function and aesthetics. Objective: To report the conservative management of a discolored non-vital anterior tooth using non-surgical endodontic retreatment and the walking bleach technique. Case Report: A 24-year-old female presented with a complaint of anterior tooth discoloration persisting for the past two years, affecting her appearance. Patient experienced spontaneous pain five years earlier while undergoing orthodontic treatment. Six months earlier, the patient had undergone an incomplete root canal treatment, with radiographic examination revealing a non-hermetic obturation. Clinical examination revealed tenderness to percussion on tooth #11 and radiographic evaluation confirmed inadequate canal filling. According to the American Association of Endodontists (AAE) diagnostic criteria, tooth #21 was diagnosed as previously treated with symptomatic apical periodontitis. Non-surgical endodontic retreatment was performed with interim calcium hydroxide medication. The canal was obturated using the warm vertical compaction technique in combination with a bioceramic sealer to ensure tight seal. Bleaching was carried out using the walking bleach technique with 35% hydrogen peroxide. After the colour improved the tooth was restored with composite resin. Follow-up showed favourable aesthetic outcomes and patient satisfied with the result. Conclusion: Non surgery endodontic retreatment combined with intra-coronal bleaching using 35% hydrogen peroxide is an effective and conservative approach for managing discoloration of non-vital anterior teeth with a history of inadequate treatment.